2012
DOI: 10.1353/csd.2012.0065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Racial Identity and Gender Role Conflict to Self-Esteem of Asian American Undergraduate Men

Abstract: The purpose of this quantitative, correlational, online study was to examine the relationships of racial identity and gender-role conflict to self-esteem of Asian American undergraduate men (N = 173). Instruments included the People of Color Racial Identity Attitude Scale, Gender-Role Conflict Scale, Rosenberg Self-Esteem Scale, and a demographic questionnaire. Random samples were drawn from two large public research institutions on the East and West coasts. The two samples were combined because there were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…While many scholars have called for ethnic disaggregation in research on Asian Americans, this study and others have found intriguing gender differences that have yet been well explored by research. While some scholarship exploring gender and Asian American college students has been published (Maramba, 2008;Shek & McEwen, 2012;Tran & Chang, 2013), there remains little research providing in-depth understandings of any differences between the experiences of Asian American men and women in the college choice processes.…”
Section: Discussionmentioning
confidence: 99%
“…While many scholars have called for ethnic disaggregation in research on Asian Americans, this study and others have found intriguing gender differences that have yet been well explored by research. While some scholarship exploring gender and Asian American college students has been published (Maramba, 2008;Shek & McEwen, 2012;Tran & Chang, 2013), there remains little research providing in-depth understandings of any differences between the experiences of Asian American men and women in the college choice processes.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also suggested the importance of addressing the intersectionality of identities in Asian American students’ development (the unique intersectionality of ethnicity and race has already been addressed earlier in the chapter). Gender in particular has influenced differential experiences with racism (Museus & Park, ; Shek & McEwen, ; Tran & Chang, ) and family expectations (Maramba, , ; Ruzicka, ). For example, Asian American women often receive gendered expectations about their future role as a wife, mother, cultural transmitter, and caregiver (Maramba, ; Ruzicka, ), which may influence not only their academic and career paths but self‐efficacy and sense of self differently from that of Asian American men.…”
Section: Changing Perspectives On Student Developmentmentioning
confidence: 99%
“…Asian American studies’ scholars have extensively documented the bifurcated gender stereotypes of Asian Americans, which characterize males as asexual nerds and females as hypersexualized “dragon ladies” (Hong, ; Ono & Pham, ; Parrenas‐Shimizu, , ). For Asian American men, a higher cognitive awareness of discrimination, both racially and on a gendered level, is negatively related to self‐esteem (Shek & McEwen, ). Within the frame of an Asian American gay, lesbian, and bisexual (GLB) identity, Narui () explain GLB students’ “double minority” status and that the identity is based on a student's perception of her/his environment on a macro and micro level (e.g., university versus classroom and community versus residence hall) rather than a linear identity progression that evolves from a state of tragic dissonance to a state of universal acceptance.…”
Section: Influential Factors In the Asian American And Pacific Islandmentioning
confidence: 99%